2011
DOI: 10.1001/jama.2011.1653
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and Anticoagulant Therapy in Patients With Gastrointestinal Bleeding

Abstract: Bleeding in the upper gastrointestinal tract is a common medical problem, with an incidence of 48 to 160 cases per 1000 adults per year and a mortality rate of 5% to 14%. The risk of gastrointestinal bleeding is increased with the use of antiplatelet medications including aspirin and clopidogrel, as well as warfarin or a combination of these medications. The recurrence rate for bleeding in patients who continue to take aspirin after an episode of peptic ulcer disease-related bleeding can reach up to 300 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
1
15
1
Order By: Relevance
“…Temporary discontinuation of antithrombotic therapy is often necessary to control the bleeding and to prevent an early relapse (15). According to current evidence, the use of APAs as a secondary prophylaxis should be reinitiated as soon as possible after the episode of NVUGB (28), even if this would increase the rebleeding rate as it can potentially reduce overall mortality (29) and its discontinuation increases the risk of death and acute cardiovascular events by around sevenfold (30). In these cases, the protective effect of APAs exceeds their potential gastrotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary discontinuation of antithrombotic therapy is often necessary to control the bleeding and to prevent an early relapse (15). According to current evidence, the use of APAs as a secondary prophylaxis should be reinitiated as soon as possible after the episode of NVUGB (28), even if this would increase the rebleeding rate as it can potentially reduce overall mortality (29) and its discontinuation increases the risk of death and acute cardiovascular events by around sevenfold (30). In these cases, the protective effect of APAs exceeds their potential gastrotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…They are resuscitation, risk assessment, preendoscopic care, endoscopic management, and postendoscopic care including pharmacological and nonpharmacological therapies. The issue of secondary prophylaxis will not be addressed in this particular paper, but readers are referred to a recent narrative review on the topic [7]. …”
Section: Introductionmentioning
confidence: 99%
“…12 A recent retrospective cohort study involving 442 patients found that patients who resumed warfarin therapy within 90 days of upper gastrointestinal bleeding (median resumption of 4 d) had de creased overall mortality and thrombosis without an increased risk of recurrent gastrointestinal bleeding. 13 Considering this limited evidence and the low-risk findings on endoscopy, the patient was comfortable restarting warfarin four days later.…”
mentioning
confidence: 99%